2019
DOI: 10.3390/met9020168
|View full text |Cite
|
Sign up to set email alerts
|

Devolatilization Kinetics of Different Types of Bio-Coals Using Thermogravimetric Analysis

Abstract: The interest of the steel industry in utilizing bio-coal (pre-treated biomass) as CO2-neutral carbon in iron-making is increasing due to the need to reduce fossil CO2 emission. In order to select a suitable bio-coal to be contained in agglomerates with iron oxide, the current study aims at investigating the thermal devolatilization of different bio-coals. A thermogravimetric analyzer (TGA) equipped with a quadrupole mass spectrometer (QMS) was used to monitor the weight loss and off-gases during non-isothermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…This may affect the release of H 2 O during reaction as the ion current for H 2 O is highest for FRC although that the H-content is similar as for SDC. The impact of ash composition on the devolatilization behavior of bio-coals was indicated in a previous study [28] where bio-coal with a higher content of catalyzing components released the VM at lower temperature, and this may restrict its contribution to the reduction. High intensity of H 2 O followed by CO 2 and H 2 detected in QMS analyses for FRC indicates that some of the CO is consumed in the reaction.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This may affect the release of H 2 O during reaction as the ion current for H 2 O is highest for FRC although that the H-content is similar as for SDC. The impact of ash composition on the devolatilization behavior of bio-coals was indicated in a previous study [28] where bio-coal with a higher content of catalyzing components released the VM at lower temperature, and this may restrict its contribution to the reduction. High intensity of H 2 O followed by CO 2 and H 2 detected in QMS analyses for FRC indicates that some of the CO is consumed in the reaction.…”
Section: Discussionmentioning
confidence: 89%
“…Carbonaceous materials used are stated in Table 1, their proximate and ultimate analysis as analyzed by ALS Scandinavia AB using standard methods are presented in Table 2 and the composition of other raw materials can be seen in Table 3. The ash composition in bio-coal materials was reported in detail in a previous study [28], c.f. Table 4.…”
Section: Materials and Characterizationmentioning
confidence: 99%
“…This Special Issue published 33 high quality articles from 10 countries (according to the country of the corresponding author) with the number of contributions in brackets: China (22) , Japan (1) [23], Korea (1) [24], Canada (1) [25], Sweden (2) [26,27], Italy (1) [28], UK (1) [29], France (1) [30], Austria (1) [31], and Slovakia (2) [32,33]. This clearly reflects the enormous investment in R&D in China and the resultant outstanding outcomes to support its steel industry with~50% of global steel production.…”
Section: Contributionsmentioning
confidence: 99%
“…A UK-Netherland-USA contribution (Slater et al [29]) studied the solidification phenomena of a molten steel surface by using infrared thermography and a Sweden-Russia contribution (Sidorova et al [27]) reported the modification of non-metallic inclusions in oil-pipeline steels by Ca-treatment. A paper co-authored by scientists from Sweden and Egypt (El-Tawil et al [26]) investigated the thermal devolatilisation of different bio-coals for the purpose of reducing fossil CO 2 emission in the steel industry. Other international collaborations include France-Canada-Albania (Kanari et al [30]), Slovakia-Czech Republic (Neslušan et al [33]), China-Ukraine (Cao et al [1]), and China-UK (Ge et al [2]).…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation